Social interaction between rural residents or natives and housing residents as newcomers in Baki District, Sukoharjo Regency - Marhamah, Zahrawati; Nurhadi, Nurhadi; Pudyastuti, Septina Galih (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
As the population increases, the need for land for settlements also increases. The development of residential areas has entered rural areas and has led to an increase in the number of residents in village areas where housing was built. The meeting of two or several individuals in an area will lead to the possibility of interaction. This study aims to look at the acceptance of villagers for the presence of migrants as residents who inhabit residential areas from the aspect of social interaction. This research used a qualitative descriptive approach with data collection techniques in the form of in-depth interviews and determining sources using purposive sampling techniques. The data collection results were processed using source triangulation and member-checking and analyzed using thematic analysis methods based on the theory of social interaction by Georg Simmel. This research was carried out in two places, namely Ngrombo village and Waru village in Baki District. The research was conducted in 2023. The findings in this study found various forms of social interaction that occurred in the community in the Baki District area. Interactions between the residents of the village and the residents of the residential area are established through exchanges, superordination, subordination, and conflicts.